Evaluation of podoplanin expression in vulvar squamous cell carcinoma and stromal fibroblasts and its prognostic implications - Gilbert Georg Klamminger; Meletios P. Nigdelis; Annick Bitterlich; Mariam Parvanta; Martin Ertz; Laura Schnöder; Bernd Holleczek; Roxana Schwab; Annette Hasenburg; Bashar Haj Hamoud; Erich Franz Solomayer; Mathias Wagner (Scientific Reports)
Abstract Although the immunohistochemical expression of the transmembrane sialoglycoprotein podoplanin (D2-40) has been repeatedly reported as a factor of prognosis in various tumor entities—its potential prognostic relevance in squamous cell carcinomas of the vulva remains to be evaluated. In the present study, we evaluated 68 patients with primary vulvar carcinomas (VC) and analyzed the cytoplasmic/membranous immunohistochemical expression of podoplanin in viable tumor cells and cancer-associated fibroblasts (CAFs) within the adjacent peritumoral stroma. To determine potential associations between podoplanin expression and traditional clinicopathological parameters (e.g., tumor stage, infiltration depth, groin lymph node metastasis), as well as with local recurrences, metastases, and patient’s overall survival, subsequent data analysis was conducted using Spearman correlation analysis, Fisher’s exact test and the log-rank test (Mantel-Cox). Although our results did not substantiate a positive correlation of podoplanin expression in tumor cells or CAFs with traditional histomorphological parameters, we propose a prognostic potential of podoplanin as a tissue-based biomarker in HPV-associated VC. In our exploratory pilot study, we observed a significantly improved overall survival in this distinct subgroup (Log-rank (Mantel-Cox) test; p = 0.0399). The results of our retrospective study may support the expectations that podoplanin, a common and widely available antibody, could be used as a tool for prognostic purposes in the future. Further research and validation are necessary before these markers can be implemented in clinical practice.